Masalah Utama Ekonomi Indonesia: Tantangan Bagi Rezim Pemerintahan 2004-2009 - Hamid, Edy Suandi (Unisia, 2016)
The main problem of Indonesian economy for the next five years is not so different from that of nowadays. The problems that mentioned above are dealing with how to overcome poverty, to increase economic growth, to enlarge vocation, to build human resources., and besides, to decrease corruption. To solve those problems of this nation does not enough only a period of government and using abstract jargons. For that reason, next regime needs a clear cut explanation, planned and listed of economic agendas. So that, these economic agendas can show program that observed and clear targets.